Microglia in Alzheimer’s Disease: Activated, Dysfunctional or Degenerative - Navarro, Victoria; Sanchez-Mejias, Elisabeth; Jimenez, Sebastian; Muñoz-Castro, Clara; Sanchez-Varo, Raquel; Davila, Jose C.; Vizuete, Marisa; Gutierrez, Antonia; Vitorica, Javier (Frontiers in Aging Neuroscience, 2018)
Microglial activation has been considered a crucial player in the pathological process of multiple human neurodegenerative diseases. In some of these pathologies, such as Amyotrophic Lateral Sclerosis or Multiple Sclerosis, the immune system and microglial cells (as part of the cerebral immunity) play a central role. In other degenerative processes, such Alzheimer´s disease (AD), the role of microglia is far to be elucidated. In this “mini-review” we briefly highlight our recent data comparing the microglial response between amyloidogenic transgenic models, such as APP/PS1, and AD patients. Since the AD pathology could display regional heterogeneity, we focus our work at the hippocampal formation. In APP based models a prominent microglial response is triggered around A plaques. These strongly activated microglial cells could drive the AD pathology and, in consequence, could be implicated in the neurodegenerative process observed in models. On the contrary, the microglial response in human samples is, at least, partial or attenuated. This patent difference could simple reflect the lower and probably slower A production observed in human hippocampal samples, in comparison with models, or could reflect the consequence of a chronic long-standing microglial activation. Beside this differential response, we also observed microglial degeneration in Braak V-VI individuals that, indeed, could compromise their normal role of surveying the brain environment and respond to the damage. This microglial degeneration, particularly relevant at the dentate gyrus, might be mediated by the accumulation of toxic soluble phospho-tau species. The consequences of this probably deficient immunological protection, observed in AD patients, are unknown.